Isolation of a promising antidiabetic compound from the leaves of tetracera indica merr., and in vivo toxicological studies in diabetes induced experimental animals - Ahmed, Qamar Uddin; Afrin, Mehnaz; Mat So'ad, Siti Zaiton; Wan Sulaiman, Wan Azizi; Bakhtiar, M. Taher; Latip, Jalifah; Saxena, Anil Kumar (2014)
Diabetes mellitus is a chronic disorder together with other metabolic abnormalities, usually developed due to insulin resistance or deficiency as well as increased hepatic glucose output [1]. The prevalence of diabetes mellitus among Malaysians adults more than 30 years of age has escalated by more than two fold over a 20-year period [2]. On the other hand, many plants have been used for the treatment of diabetes mellitus in modern system of medicine and in other ancient systems of the world. As a result, plants are now-a-days regarded as promising and significantly attractive natural sources to enrich the current therapy options against diabetes. However, so far, not many active agents have been successfully isolated and extensively studied [3]. Hence, we prompted to evaluate the antidiabetic potential of a flavonoid (5,7-dihydroxy-8-methoxyflavone [4], Figure 1) isolated from the leaves of Tetracera indica Merr., a Malaysian medicinal plant which is traditionally used to treat diabetes in Malaysia. The study was carried out using Sprague-Dawley rats (diabetic as well as normal) to evaluate antidiabetic potential of 5,7-dihydroxy-8-methoxyflavone at three different concentrations, viz. 1 mg/kg b.w., 5 mg/kg b.w. and 25 mg/kg b.w. At 5 mg/kg b.w. and 25 mg/kg b.w., it was found to exhibit significant anti-hyperglycemic activity in alloxan induced diabetic rats and in normal rats, no hypoglycemic activity was observed at all concentrations, when compared with +ve and –ve controlled groups. The antidiabetic activity was found to be comparable with glibenclamide (GLBC), a known oral hypoglycemic agent (50 mg/kg b.w.) (Table 1). The LD50 of 5,7-dihydroxy-8-methoxyflavone was found to be more than 500 mg/kg b.w. and no lethal toxicity was observed within this range. Three weeks later, the in-vivo study, histopathology of kidney and pancreas from alloxan-induced rats demonstrated the clinical manifestation of diabetic affected kidney and pancreas (Figures 2 & 3). It is concluded that the 5,7-dihydroxy-8-methoxyflavone from the leaves of T. indica is a safe and promising antidiabetic agent that could prove useful in the management of diabetes and might also provide lead for the synthesis of a new class of safe antidiabetic drugs. Keywords: 5,7-dihydroxy-8-methoxyflavone, Tetracera indica, antidiabetic agent